2012
DOI: 10.3390/molecules17022178
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Nozzle/Diffuser Micropumps with Novel Valves

Abstract: This study conducts an experimental study concerning the improvement of nozzle/diffuser micropump design using some novel no-moving-part valves. A total of three micropumps, including two enhancement structures having two-fin or obstacle structure and one conventional micro nozzle/diffuser design, are made and tested in this study. It is found that dramatic increase of the pressure drops across the designed micro nozzles/diffusers are seen when the obstacle or fin structure is added. The resultant maximum flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 22 publications
0
15
0
1
Order By: Relevance
“…Ullmann et al [13] studied performance of valveless micropumps of different configurations including parallel and series connection of multiple micropumps. Yang et al [14] presented an improved design of valveless micropump without any moving parts. Guo et al [15] reported a parallel double chamber as a modification to the basic valveless micropump design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ullmann et al [13] studied performance of valveless micropumps of different configurations including parallel and series connection of multiple micropumps. Yang et al [14] presented an improved design of valveless micropump without any moving parts. Guo et al [15] reported a parallel double chamber as a modification to the basic valveless micropump design.…”
Section: Introductionmentioning
confidence: 99%
“…From the literature review, it is clear that experimental investigations of PZT actuated valveless micropumps including microfabrication and experiments have been reported by various research groups in the past few years [11][12][13][14][15][16][17][18][19][20][21]. Also, many approximate analytical and simulation models have been reported [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the difference in hydrodynamic resistance of the nozzle and the diffuser a unidirectional net flow is induced in the microfluidic system. Since no moving parts are encountered with these elements, wear and fatigue are eliminated with the drawback of low efficiency compared to check-valves or other active valves [4]. A typical realization of such a valve-less micropump in glass technology is given in [5].…”
Section: Introductionmentioning
confidence: 99%
“…Microfluidic pumps are key parts for the development of highly integrated LOC and μTAS systems. Peristaltic membrane pumps utilizing nozzle-diffuser structures, which number among the mechanical displacement pumps [3], are typically designed in such a way that the movable membrane induces pressure strokes on a fluid volume and the geometrical shape of inlet and outlet resembles a nozzle and a diffuser structure [4], respectively. Here geometrical constrictions and widenings of the fluid channel are used as flow directing elements.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, µTAS are expected to be applied in point-of-care testing, where a chemical or biochemical test is performed and results are obtained immediately. Several microfluidic devices have been developed for the µTAS, such as micropumps [1,2], micromixers [3,4], and microvalves [5,6]. In particular, microvalves play an important role in fluid control and sample sorting in the µTAS.…”
Section: Introductionmentioning
confidence: 99%